The Influence of Service Quality and Product Quality on Member Satisfaction of Koperasi Simpan Pinjam CU Karya Bersama - Yasin Nur Rohim; Felik Sad Windu Winu Broto; Bernadeta Helen Santoso (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study analyzes the effect of service quality and product quality on member satisfaction at Koperasi Simpan Pinjam CU Karya Bersama with a quantitative research type. This study used multiple linear regression analysis with a population of 213 active members in the loan product data of KoperasiSimpanPinjam CU Karya Bersama and a sample of 140 respondents. The data collection method used was a questionnaire. The results show that the regression equation Y = 4.871 + 0.319 X1 + 0089 X2 + e The independent variables of service quality and product quality simultaneously influence the satisfaction of members of Koperasi Simpan Pinjam CU Karya Bersama. Service quality and product quality variables affect member satisfaction, with a value of 36.3. While the remaining 63.7% (100%-36.3) = 63.7% are other variables not mentioned in this study, such as corporate image, promotion, and motivation.